IMPLEMENTASI KEBIJAKAN TAMAN HUTAN RAYA (TAHURA) SULTAN SYARIF HASYIM OLEH DINAS KEHUTANAN PROVINSI RIAU - Fauzan, Ardhi; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
the importance of sustainable forest management and community welfare, the Riau Provincial Government through Regional Regulation No. 5 of 2015 on the Management of Sultan Syarif Hashim, has established UPH KPHP Minas Tahura which is the Technical Implementation Unit (UPT) of Riau Forestry Service .This study aims to find out implementation of Forest Park policy (Tahura) Sultan Syarif Hasyim by Riau Forestry Department. This research uses qualitative research method with descriptive research type. This method aims to get a true picture of the management of Forest Park (Tahura) Sultan Syarif Hasyim by Riau Forestry Service .This study found that the implementation of Forest Park policy (Tahura) Sultan Syarif Hasyim By Riau Forestry Service from the communication aspect has been running optimally. Viewed from the aspect of resources, UPH KPHP Minas Tahura staff is still less than only 15 people, but in terms of quality is very adequate because previously had followed the trainings. From the disposition aspect, the placement of UPH KPHP Minas Tahura staffs in accordance with their respective fields and expertise. Viewed from the bureaucratic structure can work well together.Keywords: Policy Implementation, Tahura , SSH .